Graphite composite material and preparation method thereof, negative electrode and battery

By covering the borate-based polymer on the surface of the graphite matrix of the graphite negative electrode material to form a polymer network structure, the problem of increasing internal impedance of graphite negative electrode material in lithium-ion batteries due to the generation of SEI film and by-product impurities is solved, and the effect of improving electrochemical performance and extending the battery cycle life is achieved.

CN119764360APending Publication Date: 2025-04-04HUIZHOU BYD BATTERY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411034669.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials increase internal impedance during the lithium-ion battery working cycle due to the generation of SEI film and by-product impurities, which affects the cycle life of the battery. The graphite lattice structure affected by stress is easily damaged, resulting in deterioration of electrical properties.

Method used

Graphite composite materials are used, in which the surface of the graphite matrix is ​​coated with borate-based polymer, and a polymer network structure is formed through in-situ coating reaction, which repairs graphite surface defects, reduces side reactions, and forms a stable artificial SEI film.

Benefits of technology

The mechanical strength, chemical stability and strain resistance of graphite negative electrode materials are improved, the mechanical strength and stability of SEI films are enhanced, the consumption of film-forming lithium is reduced, and the electrochemical performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764360A_ABST
    Figure CN119764360A_ABST
Patent Text Reader

Abstract

The invention relates to a graphite composite material and a preparation method thereof, a negative electrode and a battery. The graphite composite material comprises a graphite matrix and a borate-based polymer coated on the surface of the graphite matrix. The graphite composite material provided by the invention has more excellent electrochemical performance in battery application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of new energy technology, and in particular, to a graphite composite material and a preparation method thereof, a negative electrode and a battery. Background Art

[0002] With the rapid development of new energy vehicles, the installation volume of lithium-ion power batteries continues to set new records, and higher performance requirements are also put forward for lithium-ion batteries. As for graphite negative electrodes, during the working cycle of lithium-ion batteries, the graphite layer structure will be filled with SEI films and a large number of by-product impurities generated by reactions with electrolyte components, which will increase the internal impedance and thus affect the cycle life of the battery. At the same time, affected by a variety of stress factors, the lattice structure of the graphite itself will also be damaged or even peeled off, resulting in serious degradation of electrical performance. Therefore, the electrochemical properties of existing graphite negative electrode materials (such as first coulomb efficiency, cycle stability, etc.) still need to be further improved. Summary of the invention

[0003] The purpose of the present disclosure is to provide a graphite composite material and a preparation method thereof, a negative electrode and a battery, which can further improve the electrochemical performance of graphite negative electrode materials in battery applications.

[0004] In order to achieve the above-mentioned object, the present disclosure provides a first aspect of a graphite composite material, comprising a graphite matrix and a borate-based polymer coated on the surface of the graphite matrix.

[0005] Optionally, the borate-based polymer has a repeating unit represented by the following formula (1): Formula (1); Wherein R1 is one of hydroxyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C1-C12 alkyl; the substituent of R1 is selected from halogen, C1-C5 alkyl, carboxyl, amino or C7-C10 aromatic acyl; R2 is one of a substituted or unsubstituted alkylene group, a substituted or unsubstituted polyglycol segment, and a substituted or unsubstituted polyenol segment.

[0006] Optionally, based on the total weight of the graphite composite material, the content of the graphite matrix is ​​95-99.5% by weight, and the content of the borate-based polymer is 0.5-5% by weight; the graphite matrix includes recycled graphite.

[0007] Optionally, the borate-based polymer further comprises nitrogen; based on the total weight of the borate-based polymer, the content of the nitrogen is 1 to 20 wt %.

[0008] Optionally, the graphite composite material has a D 50The particle size is 8~20μm, and the BET specific surface area is 1~4m 2 / g, and the coating thickness of the borate-based polymer is 5-50nm.

[0009] A second aspect of the present disclosure provides a method for preparing a graphite composite material, comprising the following steps: The borate-based polymer is contacted with a graphite substrate in a solvent to perform an in-situ coating reaction on the surface of the graphite substrate.

[0010] Optionally, the borate-based polymer has a repeating unit represented by the following formula (1): Formula (1); Wherein R1 is one of hydroxyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C1-C12 alkyl; the substituent of R1 is selected from halogen, C1-C5 alkyl, carboxyl, amino or benzoyl; R2 is a substituted or unsubstituted alkylene group, a substituted or unsubstituted polyglycol segment, or a substituted or unsubstituted polyenol segment.

[0011] Optionally, the graphite matrix comprises recycled graphite; the D of the recycled graphite 50 The particle size is 8~21μm, and the BET specific surface area is 2~6 m 2 / g; The solvent is selected from one or more of alcohol solvents and ether solvents; the alcohol solvent is selected from one or more of methanol, ethanol and isopropanol; the ether solvent is selected from one or more of ethyl ether, dipropyl ether, diisopropyl ether and ethyl butyl ether.

[0012] Optionally, the method comprises the following steps: a. first mixing a boric acid monomer and a polyol monomer in a solvent; then heating the solvent to a polycondensation reaction temperature, adding an azeotropic agent, and performing a polycondensation reaction to obtain a reaction mixture; b. Adding the graphite matrix into the reaction mixture to carry out a surface coating reaction of the graphite matrix.

[0013] Optionally, the boronic acid monomer is selected from one or more of boric acid, 2-fluorophenylboric acid, 3-fluorophenylboric acid, 4-ethylphenylboric acid, 4-methylphenylboric acid, 3-carboxyphenylboric acid, 4-carboxyphenylboric acid, 4-benzoylphenylboric acid and 4-carboxy-3-fluorophenylboric acid; The polyol monomers include polyol compounds and polyol polymers; the polyol compound is selected from one or more of ethylene glycol, 1,3-propylene glycol, 2,3-butylene glycol, neopentyl glycol and dipropylene glycol; The polyol polymer is selected from one or more of polyethylene glycol, polypropylene glycol, polyvinyl alcohol and polytetramethylene glycol.

[0014] Optionally, the boric acid monomer further includes a nitrogen-containing boric acid compound; the nitrogen-containing boric acid compound is selected from one or more of 3-aminophenylboric acid, 3-amino-4-fluorophenylboric acid and 4-(N,N-dimethylamino)phenylboric acid; the polyol monomer further includes a polyol amine compound; the polyol amine compound is selected from one or more of triethanolamine, diethanolamine, trimethanolamine and triisopropanolamine.

[0015] Optionally, the molar ratio of the boric acid monomer to the polyol monomer is 1:(0.2-5); Based on the total weight of the graphite matrix, the total amount of the boric acid monomer and the polyol monomer is 0.5-5% by weight of the weight of the graphite matrix; Based on the weight of the solvent, the total weight of the boric acid monomer and the polyol monomer in the solvent is 1-20 weight %.

[0016] Optionally, in step a, the entrainer is selected from one or more of benzene, toluene and petroleum ether; and the volume ratio of the entrainer to water in the reaction mixture is 0.8-1.5:1.

[0017] Optionally, in step a, the conditions of the polycondensation reaction include: the polycondensation reaction temperature is 80~140°C, the polycondensation reaction pressure is 0.1~0.5MPa, and the polycondensation reaction time is 6~12h; the polycondensation reaction is carried out under an inert atmosphere, and the inert atmosphere is selected from one or both of nitrogen and argon.

[0018] Optionally, in step b, the conditions for the in-situ coating reaction on the surface of the graphite substrate include: a reaction temperature of 70-110° C. and a reaction time of 4-12 h.

[0019] A third aspect of the present disclosure provides a graphite composite material prepared according to the method described in the second aspect of the present disclosure.

[0020] A fourth aspect of the present disclosure provides a negative electrode, which includes the graphite composite material described in the first aspect or the third aspect of the present disclosure.

[0021] A fifth aspect of the present disclosure provides a battery, which includes the negative electrode described in the fourth aspect of the present disclosure.

[0022] Optionally, the battery further comprises an electrolyte; based on the total weight of the electrolyte, the content of the borate ester compound in the electrolyte is less than 200 ppm.

[0023] Through the above technical scheme, the present disclosure provides a graphite composite material and a preparation method thereof, a negative electrode and a battery. The borate-based polymer coated on the surface of the graphite matrix of the present disclosure has the characteristics of high mechanical strength and good chemical stability, which can not only repair the surface defects of graphite, reduce the specific surface area of ​​graphite, reduce the occurrence of side reactions, but also has better coating uniformity; the borate-based polymer has a polymer elastic network structure on the surface of the graphite matrix, which has better adaptability to mechanical stress, and the borate-based polymer itself can become the SEI film skeleton, so that the SEI film is attached to the borate-based polymer network structure to form, and can form a stable artificial SEI film during the battery cycle, enhance the mechanical strength, stability and strain resistance of the SEI film formed during the battery application process, make the SEI layer not easy to break, reduce the film-forming lithium consumption, and significantly improve the electrochemical performance; the borate-based polymer also has good ionic conductivity, which promotes the transmission of lithium ions in the SEI film. The method for preparing a graphite composite material provided by the present disclosure can in-situ coat the borate-based polymer on the surface of the graphite matrix, and can be treated at low temperature, without high temperature carbonization, low cost, and easy to mass produce.

[0024] Other features and advantages of the present disclosure will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings are used to provide a further understanding of the present disclosure and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present disclosure but do not constitute a limitation of the present disclosure. In the accompanying drawings: Figure 1 This is a SEM electron microscope photograph of the graphite composite material prepared in Example 1 of the present disclosure. DETAILED DESCRIPTION

[0026] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.

[0027] A first aspect of the present disclosure provides a graphite composite material, comprising a graphite matrix and a borate-based organic compound coated on a surface of the graphite matrix.

[0028] The present disclosure provides a graphite composite material, in which a borate-based polymer coated on the surface of a graphite matrix has the characteristics of high mechanical strength and good chemical stability, and can not only repair surface defects of graphite, reduce the specific surface area of ​​graphite, and reduce the occurrence of side reactions, but also has better coating uniformity; the borate-based polymer has a polymer elastic network structure on the surface of the graphite matrix, and has better adaptability to mechanical stress; the borate-based polymer itself can become a SEI film skeleton, so that the SEI film is formed by adhering to the borate-based polymer network structure, and can form a stable artificial SEI film during battery cycling, enhance the mechanical strength, stability and strain resistance of the SEI film formed during battery application, make the SEI layer not easy to break, reduce the consumption of film-forming lithium, and significantly improve the electrochemical performance; the borate-based polymer also has good ionic conductivity, and promotes the transmission of lithium ions in the SEI film.

[0029] In one embodiment, the borate-based polymer forms a network structure on the surface of the graphite matrix; the structure of the borate-based polymer includes multiple borate groups. The molecular structure of the borate-based polymer provided by the present disclosure can be a linear polymer or a branched polymer with multiple branches, which is conducive to coating on the surface of the graphite matrix to construct a polymer network.

[0030] In a preferred embodiment, the borate-based polymer has a repeating unit represented by the following formula (1): Formula (1); wherein R1 is one of hydroxyl, substituted or unsubstituted C6~C12 aryl, substituted or unsubstituted C1~C12 alkyl; the substituent of R1 is selected from halogen, C1~C5 alkyl, carboxyl, amino or C7~C10 aromatic acyl; wherein the halogen can be selected from fluorine, chlorine or bromine, the C1~C5 alkyl can be selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, etc.; the C7~C10 aromatic acyl is selected from benzoyl, phenylacetyl, phenylpropionyl, etc.; R2 is a substituted or unsubstituted alkylene group, a substituted or unsubstituted polyglycol segment, a substituted or unsubstituted polyenol segment, and the substituent of R2 is selected from conventional substituents such as alkyl, alkenyl and ether bonds. The borate-based polymer having the structure provided in this embodiment can form an organic coating structure with better effect on the graphite surface. In the present disclosure, the number of carbon atoms of the R1 and R2 groups refers to the total number of carbon atoms of the group and the substituents connected thereto, for example, C6~C12 aryl refers to the total number of carbon atoms of the aryl and the substituents connected thereto is 6~12, such as phenyl, tolyl, ethylphenyl, biphenyl, etc.; C1~C12 alkyl refers to the total number of carbon atoms of the alkyl and its substituents is 1~12, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, etc.; C1~C5 alkyl refers to the total number of carbon atoms of the alkyl and its substituents is 1~5.

[0031] In one embodiment, based on the total weight of the graphite composite material, the content of the graphite matrix is ​​95-99.5% by weight, including but not limited to 95% by weight, 95.5% by weight, 96% by weight, 96.5% by weight, 97% by weight, 97.5% by weight, 98% by weight, 98.5% by weight, 99% by weight, and 99.5% by weight; the content of the borate-based polymer is 0.5-5% by weight, including but not limited to 0.5% by weight, 1% by weight, 1.5% by weight, 2% by weight, 2.5% by weight, 3% by weight, 3.5% by weight, 4% by weight, 4.5% by weight, and 5% by weight; preferably, the content of the graphite is 97-99% by weight, and the content of the organic coating layer is 1-3% by weight. When the component contents of the graphite composite material are within the content range provided in this embodiment, especially within the preferred content range, the graphite composite material can have better battery performance.

[0032] In one embodiment, the borate-based polymer further comprises nitrogen; based on the total weight of the borate-based polymer, the content of the nitrogen is 1 to 20% by weight, including but not limited to 1% by weight, 2% by weight, 3% by weight, 4% by weight, 5% by weight, 6% by weight, 7% by weight, 8% by weight, 9% by weight, 10% by weight, 12% by weight, 14% by weight, 16% by weight, 18% by weight, and 20% by weight; preferably 2 to 19% by weight. The present disclosure introduces nitrogen into the borate-based polymer, which can improve the conductivity of the graphite composite material and is beneficial to the ion transport of the graphite composite material during battery application; when the nitrogen content in the borate-based polymer is within the range of the present embodiment, the ionic conductivity of the graphite composite material can be further improved.

[0033] In a specific embodiment, the graphite composite material has a D 50The particle size is 8 to 20 μm, for example, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc., and may be other values ​​within the above range, preferably 8 to 14 μm; the BET specific surface area is 1 to 4 m 2 / g, for example 1.0 m 2 / g, 1.5 m 2 / g, 2.0 m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.5 m 2 / g, 4.0 m 2 / g, and may also be other values ​​within the above range, preferably 1.0~3.0m 2 / g; the coating thickness of the borate-based polymer is 5 to 50 nm, such as 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc., and may be other values ​​within the above range, preferably 10 to 25 nm. The graphite composite material provided by the present disclosure has a suitable particle size and BET specific surface area; when the coating thickness of the borate-based polymer is within the range of this embodiment, the organic coating layer has suitable mechanical strength and flexibility, good uniformity and protective effect.

[0034] In a specific embodiment, the graphite matrix includes recycled graphite. The inventors of the present disclosure have found that waste graphite negative electrodes need to go through a series of necessary processing procedures before they can be put back on the market for reuse. The main treatment methods for recycling waste graphite on the current market are wet leaching and high-temperature heat treatment. The former removes metal impurities in the discarded graphite by soaking in acid or other solutions, and the latter removes binders, residual electrolytes and SEI films by high-temperature calcination, and simultaneously re-graphitizes at high temperature to reshape the graphite lattice structure. However, the performance of the recycled graphite formed on the basis of this treatment process still cannot meet the high requirements of commercial applications. There are many surface defects, large specific surface area, and more side reactions that seriously affect the first effect and cycle performance of the negative electrode. The existing method of recovering graphite through high-temperature heat treatment of carbon coating has the problems of high temperature, large energy consumption, inability to utilize residual lithium in the graphite layer, and uncontrollable graphite structure after carbonization treatment. By using recycled graphite as the graphite matrix in the graphite composite material provided by the present invention, the borate-based polymer can adsorb residual lithium ions in the graphite (e.g., waste graphite) to form a coordination compound, which can release lithium ions in battery applications, thereby achieving the recycling of residual lithium ions in the graphite and improving the recycling effect of waste graphite.

[0035] A second aspect of the present disclosure provides a method for preparing a graphite composite material, comprising the following steps: The borate-based polymer is contacted with a graphite substrate in a solvent to perform an in-situ coating reaction on the surface of the graphite substrate, wherein the graphite substrate comprises recycled graphite.

[0036] The present disclosure provides a method for preparing a graphite composite material, which can coat a borate-based polymer on the surface of a graphite matrix through a simple preparation method; wherein the borate-based polymer is in situ coated on the surface of the graphite matrix through a bonding action with a large number of hydrogen bonds existing on the surface of the graphite matrix to form a polymer network structure; the preparation method of the present disclosure can adopt low-temperature heat treatment without high-temperature carbonization, has low cost, and is easy to mass produce.

[0037] In a preferred embodiment, the borate-based polymer has a repeating unit represented by the following formula (1): Formula (1); Wherein R1 is one of hydroxyl, substituted or unsubstituted C6~C12 aryl, substituted or unsubstituted C1~C12 alkyl; the substituent is selected from halogen, C1~C5 alkyl, carboxyl, amino or C7~C10 aromatic acyl; R2 is a substituted or unsubstituted alkylene group, a substituted or unsubstituted polyglycol segment, or a substituted or unsubstituted polyenol segment. The substituent of R2 is selected from conventional groups such as alkyl, alkenyl, and ether bond.

[0038] In one embodiment, the graphite matrix comprises recycled graphite.

[0039] In a specific embodiment, the recycled graphite can be from waste graphite after pickling and heat treatment. The recycled graphite contains sheet damage, defects and possible residual lithium ions; 50 The particle size is 9~12μm, and the BET specific surface area ranges from 2~6m 2 / g, for example 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, etc., and may also be other values ​​within the above range. The method provided by the present disclosure can realize the recycling of waste graphite, and the borate-based polymer can effectively repair the defects on the surface of the recycled graphite.

[0040] In a specific embodiment, the solvent is selected from one or more of an alcohol solvent and an ether solvent; the alcohol solvent is selected from one or more of methanol, ethanol and isopropanol; the ether solvent is selected from one or more of diethyl ether, dipropyl ether, diisopropyl ether and ethyl butyl ether. The solvent used in the present disclosure will not undergo esterification reaction or polycondensation reaction with the boric acid monomer at low temperature.

[0041] In one embodiment, the method comprises the following steps: a. first mixing a boric acid monomer and a polyol monomer in a solvent; then heating the solvent to a polycondensation reaction temperature, adding an azeotropic agent; and performing a polycondensation reaction under an inert atmosphere and at a polycondensation reaction temperature to obtain a reaction mixture; b. Adding the graphite matrix into the reaction mixture to carry out a surface coating reaction of the graphite matrix.

[0042] The present invention adopts a plurality of functional organic molecules (boric acid monomers, polyol monomers) to react (condense) in a liquid phase at low temperature to generate borate ester polymers through the above step a, and then coats through step b. This process is conducive to controlling the polycondensation reaction in step a to be more complete, so as to obtain the borate ester polymer with the target structure. The addition of an azeotropic agent in step a can form an azeotropic agent-alcohol-water azeotrope, which is conducive to the removal of water.

[0043] In a specific embodiment, the boronic acid monomer is selected from one or more of boric acid, 2-fluorophenylboric acid, 3-fluorophenylboric acid, 4-ethylphenylboric acid, 4-methylphenylboric acid, 3-carboxylphenylboric acid, 4-carboxylphenylboric acid, 4-benzoylphenylboric acid and 4-carboxyl-3-fluorophenylboric acid; preferably, the boronic acid monomer is selected from one or more of boric acid, 2-fluorophenylboric acid, 3-fluorophenylboric acid, 4-methylphenylboric acid, 3-carboxylphenylboric acid and 4-carboxylphenylboric acid. The boronic acid monomer used in the present disclosure can introduce aromatic groups such as benzene rings, or introduce organic groups such as alkyl, carboxyl, carbonyl and fluorine atom substituents, so that the boronic acid monomer and the formed coating layer have good distribution uniformity, improved ionic conductivity and other effects.

[0044] In one embodiment, the polyol monomers include polyol compounds and polyol polymers; the polyol compounds are selected from one or more of ethylene glycol, 1,3-propylene glycol, 2,3-butylene glycol, neopentyl glycol and dipropylene glycol; The polyol polymer is selected from one or more of polyethylene glycol, polypropylene glycol, polyvinyl alcohol and polytetrahydrofuran diol; optionally, the number average molecular weight of the polyol polymer is 400-2000, and the molecular weight of the polyol polymer can be selected according to the preparation process. In the present disclosure, a polyol polymer and a boric acid monomer are used for polycondensation reaction, and the polymer molecular chains are cross-linked to form a cross-linked network, so that the polymerization effect is more uniform and sufficient. In addition, the polyol polymer monomer itself contains functional groups such as ether groups, which can have the effects of improving the flexibility and water resistance of the polymer network layer after forming a polymer-coated network.

[0045] In one embodiment, the boric acid monomer further comprises a nitrogen-containing boric acid compound; the nitrogen-containing boric acid compound is selected from one or more of 3-aminophenylboronic acid, 3-amino-4-fluorophenylboronic acid and 4-(N,N-dimethylamino)phenylboronic acid; the polyol monomer further comprises a polyolamine compound; preferably, the polyolamine compound is selected from one or more of triethanolamine, diethanolamine, trimethanolamine and triisopropanolamine. This embodiment introduces nitrogen-containing reaction monomers into the reaction system to obtain nitrogen-containing borate-based polymers, which is beneficial to change the charge distribution of the polymer network coated on the surface of the graphite matrix and improve the ionic conductivity of the borate-based polymer. In the present disclosure, "polyolamine compounds" refer to alcoholamine compounds containing two or more hydroxyl groups.

[0046] In a preferred embodiment, the molar ratio of the boric acid monomer to the polyol monomer is 1:(0.2~5), preferably 1:(0.5~3). By controlling the molar ratio of the added boric acid monomer to the polyol monomer, the generation of the borate-based polymer generated by the polycondensation reaction can be controlled, and then the structure and composition of the organic coating layer on the surface of the recycled graphite can be regulated to achieve controllable structure of the organic coating layer. Adding the boric acid monomer and the polyol monomer according to the preferred molar ratio in this embodiment has a better polymerization effect, a more uniform distribution of the groups, and a balance between the thickness and functionality of the coating layer.

[0047] In one embodiment, based on the total weight of the graphite matrix, the total amount of the boric acid monomer and the polyol monomer is 0.5-5% by weight of the weight of the graphite matrix, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc., and may be other values ​​within the above range; preferably 1-3% by weight; in-situ coating is performed according to the weight ratio between the graphite matrix and the total amount of the boric acid monomer and the polyol monomer provided in this embodiment, and a better graphite composite material can be obtained, and the polymer thickness is appropriate, the mechanical stability and flexibility are better, and the electrochemical performance of the composite material is better.

[0048] In a specific embodiment, based on the weight of the solvent, the total weight of the boric acid monomer and the polyol monomer in the solvent is 1-20% by weight, such as 1% by weight, 5% by weight, 10% by weight, 15% by weight, 20% by weight, or other values ​​within the above range; preferably 4-10% by weight. According to the optimized weight ratio between the reactants and the solvent provided in this embodiment, a better liquid phase polycondensation reaction effect can be achieved.

[0049] In one embodiment, in step a, the entrainer is selected from one or more of benzene, toluene and petroleum ether; the volume ratio of the entrainer to water in the reaction mixture is 0.8 to 1.5: 1, such as 0.8: 1, 1: 1, 1.25: 1, 1.5: 1, etc., and may also be other values ​​within the above range, preferably 0.8 to 1.2: 1. The addition ratio of the entrainer to water provided in this embodiment has a better effect of azeotropic removal of water.

[0050] In a specific embodiment, in step a, the conditions of the polycondensation reaction include: the polycondensation reaction temperature is 80~140°C, such as 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, etc., and can also be other values ​​within the above range; the polycondensation reaction pressure is 0.1~0.5MPa, including but not limited to 0.1MPa, 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa; the polycondensation reaction time is 6~12h, such as 6h, 8h, 10h, 12h, etc., and can also be other values ​​within the above range; the inert atmosphere is selected from one or more of nitrogen and argon; preferably, the polycondensation reaction temperature is 100~130°C, the polycondensation reaction pressure is 0.3~0.4MPa, and the polycondensation reaction time is 8~10h. The preferred polycondensation reaction conditions in this embodiment are beneficial to improving the polycondensation reaction effect.

[0051] In a specific embodiment, step a may adopt a high pressure reaction environment to promote the polycondensation reaction.

[0052] In one embodiment, in step b, the conditions of the surface in-situ coating reaction include: a reaction temperature of 70 to 110° C. and a reaction time of 4 to 12 hours; preferably, a reaction temperature of 80 to 105° C. and a reaction time of 6 to 8 hours. According to the preferred coating conditions in this embodiment, it is beneficial to obtain a better borate-based polymer coating structure on the graphite surface.

[0053] In a specific embodiment, step b also includes: distilling the product obtained from the second reaction to remove the solvent, and then drying; the drying is vacuum drying or spray drying; the vacuum drying temperature is 120~150℃; the inlet temperature of spray drying is 130~150℃, and the outlet temperature is 90~110℃.

[0054] A third aspect of the present disclosure provides a graphite composite material prepared according to the method described in the second aspect of the present disclosure.

[0055] A fourth aspect of the present disclosure provides a negative electrode, which includes the graphite composite material described in the first aspect or the third aspect of the present disclosure.

[0056] The composition and preparation of the negative electrode in the present disclosure may be conventional processes in the art.

[0057] A fifth aspect of the present disclosure provides a battery, which includes the negative electrode described in the fourth aspect of the present disclosure.

[0058] In the present disclosure, the assembly of the battery may be a conventional process in the art.

[0059] In a preferred embodiment, the electrolyte of the battery provided by the present disclosure does not need to be additionally added with a borate group compound (such as a lithium salt with a borate group), and the content of the borate group compound in the electrolyte is low; preferably, based on the total weight of the electrolyte, the content of the borate group compound in the electrolyte is less than 200 ppm. The total content of the borate group compound in the electrolyte is obtained by gas chromatography-mass spectrometry (GCMS).

[0060] The present disclosure is further described in detail by way of examples. The raw materials used in the examples can all be obtained through commercial sources.

[0061] Example 1 (1) Boric acid and polyethylene glycol were added to anhydrous ethanol solvent in a molar ratio of 1:3. The total mass of the reactants (the total mass of boric acid and polyethylene glycol) was 3 wt % of the mass of the recovered graphite, and the mass of the reactants (the total mass of boric acid and polyethylene glycol) was 5 wt % of the mass of the solvent. The mixture was stirred with a magnetic stirrer for 1 h at a speed of 600 r / min.

[0062] (2) Raise the reaction temperature to 130°C, add toluene as an azeotropic agent, introduce nitrogen as a protective atmosphere and continue the reaction for 8 hours (condensation reaction).

[0063] (3) After natural cooling, the graphite (D 50 =13um, BET specific surface area = 3.4 m 2 / g) was added into the mixed solution and stirred for 2 h, and then the solvent and residual reactants were distilled off.

[0064] (4) vacuum drying at 120° C. and cooling to obtain a recycled graphite negative electrode modified by repairing the artificial SEI film of an organic borate-based polymer (i.e., a graphite composite material in which the surface of the graphite matrix is ​​coated with a borate-based polymer).

[0065] The reaction formula of the polycondensation reaction in step (1) of this embodiment is as follows: ; where m and n are greater than 0.

[0066] The SEM electron microscope photo of the graphite composite material prepared in Example 1 is as follows Figure 1 As shown by Figure 1 It can be seen that the edges of the graphite particles after coating and modification are relatively rounded.

[0067] Example 2 Referring to the preparation method in Example 1, the difference from Example 1 is that the molar ratio of boric acid to polyethylene glycol is adjusted to 1:1, and the rest of the process is the same as Example 1.

[0068] Example 3 Referring to the preparation method in Example 1, the difference from Example 1 is that the total amount of boric acid and polyethylene glycol is 1% by weight of the weight of the recovered graphite, and the rest of the process is the same as Example 1.

[0069] Example 4 Referring to the preparation method in Example 1, the difference from Example 1 is that polyethylene glycol is replaced by polyvinyl alcohol, and the rest of the process is the same as Example 1.

[0070] Example 5 Referring to the preparation method in Example 1, the difference from Example 1 is that boric acid is replaced by 4-methylphenylboric acid, and the rest of the process is the same as Example 1.

[0071] Example 6 Referring to the preparation method in Example 1, the difference from Example 1 is that the mass of the reactants (the total amount of boric acid and polyethylene glycol) and the ratio to the solvent in step (1) are adjusted to 10 wt %, and the rest of the process is the same as Example 1.

[0072] Example 7 Referring to the preparation method in Example 1, the difference from Example 1 is that the polycondensation reaction temperature in step (2) is adjusted to 80°C, and the rest of the process is the same as Example 1.

[0073] Example 8 Referring to the preparation method in Example 1, the difference from Example 1 is that the polycondensation reaction time of step (2) is adjusted to 6 hours, and the rest of the process is the same as Example 1. Example 9 Referring to the preparation method in Example 1, the difference from Example 1 is that the total amount of boric acid and polyethylene glycol is 10% by weight of the weight of the recovered graphite, and the rest of the process is the same as Example 1.

[0074] Example 10 Referring to the preparation method in Example 1, the difference from Example 1 is that the molar ratio of boric acid to polyethylene glycol is adjusted to 1:0.125, and the rest of the process is the same as Example 1.

[0075] Embodiment 11 Referring to the preparation method in Example 1, the difference from Example 1 is that the polycondensation reaction temperature in step (2) is adjusted to 50°C, and the rest of the process is the same as Example 1.

[0076] Example 12 Referring to the preparation method in Example 1, the difference from Example 1 is that the polycondensation reaction time of step (2) is adjusted to 4 hours, and the rest of the process is the same as Example 1.

[0077] Embodiment 13 Referring to the preparation method in Example 1, the difference from Example 1 is that polyethylene glycol is replaced by triethanolamine, and the rest of the process is the same as Example 1.

[0078] Embodiment 14 Referring to the preparation method in Example 1, the difference from Example 1 is that boric acid is replaced by 3-aminophenylboronic acid, and the rest of the process is the same as Example 1.

[0079] Embodiment 15 Referring to the preparation method in Example 1, the difference from Example 1 is that the total amount of boric acid and polyethylene glycol is 0.5% by weight of the weight of the recovered graphite, and the rest of the process is the same as Example 1.

[0080] Example 16 Referring to the preparation method in Example 1, the difference from Example 1 is that the total amount of boric acid and polyethylene glycol is 5 weight percent of the weight of the recovered graphite, and the rest of the process is the same as in Example 1.

[0081] Embodiment 17 Referring to the preparation method in Example 1, the difference from Example 1 is that the molar ratio of boric acid to polyethylene glycol is adjusted to 1:0.2, and the rest of the process is the same as Example 1.

[0082] Embodiment 18 Referring to the preparation method in Example 1, the difference from Example 1 is that the molar ratio of boric acid to polyethylene glycol is adjusted to 1:5, and the rest of the process is the same as Example 1.

[0083] Comparative Example 1 The unrepaired and unmodified recovered graphite matrix in Example 1 is directly used as the negative electrode material.

[0084] Test Example 1 This test example is used to test the material properties of the products prepared in the above examples and comparative examples.

[0085] The BET specific surface area of ​​the samples prepared in the above embodiments and comparative examples was measured by nitrogen adsorption / desorption test method; the D 50The thickness of the polymer artificial SEI precursor layer (i.e., the borate-based polymer coated on the surface of the graphite matrix) of the samples prepared in the above embodiments and comparative examples was measured by transmission electron microscopy, and the test results are listed in the following Table 1. The component content in the graphite composite material product (based on the total weight of the graphite composite material) and the nitrogen content in the borate-based polymer (based on the total weight of the borate-based polymer) were calculated by the addition amount of the raw materials in the preparation process.

[0086] Table 1

[0087] According to the data in Table 1 above, we can see that: Compared with the unrepaired and modified recycled graphite in Comparative Example 1, the recycled graphite negative electrode prepared by the method provided by the present disclosure and repaired and modified by the organic borate-based polymer artificial SEI film can reduce the specific surface area to 1.65-3.02 m 2 / g;D 50 The particle size increased slightly to 13.1~13.3μm, with no significant change; the thickness of the borate-based polymer was 8~25 nm.

[0088] According to the data in Examples 9 to 12, it can be seen that: on the basis of Example 1, after changing the experimental conditions, the esterification rate of the reactants changes, and the physical properties of the obtained samples also change accordingly; when the reactants account for 10% by weight of the active material (Example 9), the borate polymer becomes significantly thicker and the BET specific surface area decreases significantly; when the amount of boric acid added as the reactant is too much (Example 10), the reaction temperature is too low (Example 11), and the reaction time is reduced (Example 12), the esterification rate decreases, and the thickness of the borate polymer observed by electron microscopy is thinner or more uneven, and has no significant effect on the D50 particle size.

[0089] According to the data of Examples 15-16, it can be seen that the addition ratio between the total amount of boric acid and polyethylene glycol and the recycled graphite in the preparation process of Examples 15-16 is not within the preferred range provided in the present disclosure, and the thickness of the borate-based polymer in the graphite negative electrode material prepared in Examples 15-16 exceeds the preferred thickness range (10-25 nm) provided in the present disclosure, or does not reach the preferred thickness range (10-25 nm) provided in the present disclosure.

[0090] Test Example 2 This test example is used to test the electrochemical performance of the products obtained in the above examples and comparative examples.

[0091] The products obtained in the above embodiments and comparative examples were mixed with carbon black, sodium carboxymethyl cellulose, and styrene-butadiene rubber in a mass ratio of 96:1.2:1:1.8, and then added to water and stirred evenly to form a negative electrode slurry. The negative electrode slurry was evenly coated on the copper foil using a coating machine, and the pole piece was placed in a vacuum drying oven at a temperature of 120°C and dried for 12 hours, and rolled to form a negative electrode. Subsequently, a CR-2025 button lithium-ion battery was assembled in a glove box filled with argon gas, with a lithium sheet as the negative electrode, a diaphragm made of polypropylene, an electrolyte solute of 1M LiPF6, and an electrolyte solvent of a mixed solution of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) (the volume ratio of the three was 1:1:1).

[0092] The first cycle coulombic efficiency, reversible specific capacity and cycle performance of the battery prepared above were tested, and the results are shown in Table 2; The first cycle coulombic efficiency test: the first cycle is 0.05C (1C=350mAh / g) constant current discharge to 0.01V, then constant voltage discharge, the cut-off current is 0.02C, and then charged to 2.0V with 0.05C constant current; the above steps are repeated for 3 cycles, and the lithium desorption capacity in the third cycle is the reversible specific capacity.

[0093] Cyclic performance test: discharge at a constant current of 0.05C to 0.01V, then discharge at a constant voltage with a cut-off current of 0.02C, and then charge at a constant current of 0.05C to 2.0V. After repeating the above steps three times, perform charge and discharge cycles at a rate of 0.2C, with a charge and discharge range of 0.01V~2.0V.

[0094] The total content of compounds with borate groups in the electrolyte was detected by gas chromatography-mass spectrometry (GCMS).

[0095] The electrochemical performance test results of the battery are listed in Table 2 below.

[0096] Table 2

[0097] According to the data in Tables 1 and 2 above, we can see that: Compared with the recycled graphite that was not repaired and modified in Comparative Example 1, the graphite composite materials prepared according to the method provided in Examples 1 to 18 have better electrochemical performance, and the first coulombic efficiency, reversible specific capacity and cycle capacity retention rate are all improved; Comparing Examples 15-16 with Example 9, in the graphite composite material preparation process, the total amount of boric acid and polyethylene glycol in the recovered graphite in Examples 15-16 is within the optimized range (0.5-5% by weight), and the reversible specific capacity and cycle capacity retention rate of the composite materials obtained in Examples 15-16 in battery applications are higher than those of the graphite composite material obtained in Example 9, and the graphite composite materials obtained in Examples 15-16 have better comprehensive performance in battery applications; Further, comparing Examples 1 and 3 with Examples 15 to 16, the total amount of boric acid and polyethylene glycol in the recycled graphite in Examples 1 and 3 is within the preferred range of 1 to 3% by weight, and the coating thickness of the borate-based polymer in the obtained graphite composite material is suitable, and the electrochemical performance is good; while the total amount of boric acid and polyethylene glycol in the recycled graphite in Examples 15 to 16 is not within the preferred range, and the graphite composite materials obtained in Examples 1 and 3 have higher first coulombic efficiency, reversible specific capacity and cycle capacity retention rate in battery applications than the graphite composite materials obtained in Examples 15 to 16; Comparing Example 1 with Example 5, after 4-methylphenylboric acid was used to replace boric acid in Example 5, the electrical performance of the graphite composite material in the battery was improved; Comparing Example 7 with Example 11, and comparing Example 8 with Example 12, the polycondensation reaction temperature in Example 7 and the polycondensation reaction time in Example 8 are within the optimized reaction condition range provided in the present disclosure, while the polycondensation reaction temperature in Example 11 and the polycondensation reaction time in Example 12 are not within the optimized range provided in the present disclosure. Compared with Examples 11-12, the battery test effect of the graphite composite materials described in Examples 7-8 is better; Comparing Example 1 with Examples 7-8, in Example 1, the polycondensation reaction was carried out according to the preferred reaction conditions provided in the present disclosure, while in Examples 7-8, after the reaction temperature dropped to 80°C and the reaction time was reduced to 6 hours, the electrical properties showed a downward trend, indicating that the reaction temperature and time have a significant effect on the conversion of borate esters. The composite material prepared by the preferred polycondensation reaction in Example 1 has higher first coulombic efficiency, reversible specific capacity and cycle capacity retention rate.

[0098] Comparing Examples 17 to 18 with Example 10, it can be seen that the molar ratio of boric acid monomers to polyol monomers in the preparation process of Examples 17 to 18 is within the optimized range provided in the present disclosure (1:0.2 to 5), and the molar ratio in Example 10 is not within this range. The graphite composite materials prepared in Examples 17 to 18 have higher first coulombic efficiency, reversible specific capacity and cycle capacity retention rate in battery applications; further, comparing Examples 17 to 18 with Example 1, the molar ratio of boric acid monomers to polyol monomers in Example 1 is within the further preferred range provided in the present disclosure (1:0.5 to 3), and the first coulombic efficiency, reversible specific capacity and cycle capacity retention rate of the graphite composite material prepared in Example 1 in battery applications are higher than those of the graphite composite materials prepared in Examples 17 to 18.

[0099] The results of gas chromatography-mass spectrometry tests showed that the graphite composite materials obtained in Examples 1 to 18 of the present disclosure were used in batteries, and the content of borate compounds in the electrolyte was less than 200 ppm.

[0100] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.

[0101] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.

[0102] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.

Claims

1. A graphite composite material, characterized in that: The invention comprises a graphite matrix and a borate-based polymer coated on the surface of the graphite matrix.

2. The graphite composite material according to claim 1, characterized in that The borate-based polymer has a repeating unit represented by the following formula (1): Formula (1); Wherein R1 is one of hydroxyl, substituted or unsubstituted C6-C12 aryl, substituted or unsubstituted C1-C12 alkyl; the substituent of R1 is selected from halogen, C1-C5 alkyl, carboxyl, amino or C7-C10 aromatic acyl; R2 is one of a substituted or unsubstituted alkylene group, a substituted or unsubstituted polyglycol segment, and a substituted or unsubstituted polyenol segment.

3. The graphite composite material according to claim 1, characterized in that: Based on the total weight of the graphite composite material, the content of the graphite matrix is ​​95-99.5% by weight, and the content of the borate-based polymer is 0.5-5% by weight; the graphite matrix includes recycled graphite.

4. The graphite composite material according to claim 1, characterized in that: The borate-based polymer further comprises nitrogen; based on the total weight of the borate-based polymer, the content of the nitrogen is 1 to 20 wt %.

5. The graphite composite material according to claim 1, characterized in that: The graphite composite material D 50 The particle size is 8~20μm, and the BET specific surface area is 1~4m 2 / g, and the coating thickness of the borate-based polymer is 5-50nm.

6. A method for preparing a graphite composite material, characterized in that: The following steps are involved: The borate-based polymer is contacted with a graphite substrate in a solvent to perform an in-situ coating reaction on the surface of the graphite substrate.

7. The method according to claim 6, characterized in that The borate-based polymer has a repeating unit represented by the following formula (1): Formula (1); Wherein R1 is one of hydroxyl, substituted or unsubstituted C6~C12 aryl, substituted or unsubstituted C1~C12 alkyl; the substituent of R1 is selected from halogen, C1~C5 alkyl, carboxyl, amino or benzoyl; R2 is a substituted or unsubstituted alkylene group, a substituted or unsubstituted polyglycol segment, or a substituted or unsubstituted polyenol segment.

8. The method according to claim 6, characterized in that The graphite matrix includes recycled graphite; the D 50 The particle size is 8~21μm, and the BET specific surface area is 2~6 m 2 / g; The solvent is selected from one or more of alcohol solvents and ether solvents; the alcohol solvent is selected from one or more of methanol, ethanol and isopropanol; the ether solvent is selected from one or more of ethyl ether, dipropyl ether, diisopropyl ether and ethyl butyl ether.

9. The method according to claim 6, characterized in that The method comprises the following steps: a. first mixing a boric acid monomer and a polyol monomer in a solvent; then heating the solvent to a polycondensation reaction temperature, adding an azeotropic agent, and performing a polycondensation reaction to obtain a reaction mixture; b. Adding the graphite matrix into the reaction mixture to carry out a surface coating reaction of the graphite matrix.

10. The method according to claim 9, characterized in that The boronic acid monomer is selected from one or more of boric acid, 2-fluorophenylboric acid, 3-fluorophenylboric acid, 4-ethylphenylboric acid, 4-methylphenylboric acid, 3-carboxyphenylboric acid, 4-carboxyphenylboric acid, 4-benzoylphenylboric acid and 4-carboxy-3-fluorophenylboric acid; The polyol monomers include polyol compounds and polyol polymers; the polyol compound is selected from one or more of ethylene glycol, 1,3-propylene glycol, 2,3-butylene glycol, neopentyl glycol and dipropylene glycol; The polyol polymer is selected from one or more of polyethylene glycol, polypropylene glycol, polyvinyl alcohol and polytetramethylene glycol.

11. The method according to claim 10, characterized in that The boric acid monomers also include nitrogen-containing boric acid compounds; the nitrogen-containing boric acid compounds are selected from one or more of 3-aminophenylboric acid, 3-amino-4-fluorophenylboric acid and 4-(N,N-dimethylamino)phenylboric acid; the polyol monomers also include polyol amine compounds; the polyol amine compounds are selected from one or more of triethanolamine, diethanolamine, trimethanolamine and triisopropanolamine.

12. The method according to claim 9, characterized in that The molar ratio of the boric acid monomer to the polyol monomer is 1:(0.2-5); Based on the total weight of the graphite matrix, the total amount of the boric acid monomer and the polyol monomer is 0.5-5% by weight of the weight of the graphite matrix; Based on the weight of the solvent, the total weight of the boric acid monomer and the polyol monomer in the solvent is 1-20 weight %.

13. The method according to claim 9, characterized in that In step a, the entrainer is selected from one or more of benzene, toluene and petroleum ether; the volume ratio of the entrainer to water in the reaction mixture is 0.8-1.5:

1.

14. The method according to claim 9, characterized in that In step a, the conditions of the polycondensation reaction include: the polycondensation reaction temperature is 80-140° C., the polycondensation reaction pressure is 0.1-0.5 MPa, and the polycondensation reaction time is 6-12 h; the polycondensation reaction is carried out under an inert atmosphere, and the inert atmosphere is selected from one or both of nitrogen and argon.

15. The method according to claim 9, characterized in that In step b, the conditions for the in-situ coating reaction on the surface of the graphite substrate include: a reaction temperature of 70-110° C. and a reaction time of 4-12 hours.

16. A graphite composite material prepared according to the method according to any one of claims 6 to 15.

17. A negative electrode, characterized in that: A graphite composite material comprising any one of claims 1 to 5 and 16.

18. A battery, characterized in that: The negative electrode according to claim 17 is included.

19. The battery according to claim 18, characterized in that The battery also includes an electrolyte; based on the total weight of the electrolyte, the content of the borate ester compound in the electrolyte is less than 200 ppm.

Citation Information

Cited By

  • Carbon graphite material as well as preparation method and application thereof

    CN121573987A